2009
DOI: 10.1080/10807030802615543
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Disturbances: The Missing Link between Sub-Organismal and Supra-Organismal Responses to Stress? Prospects Based on Aquatic Research

Abstract: Bridging the gap between early, sensitive responses to stress at the infra-organismal levels and long-term, ecologically relevant responses at the supra-organismal levels is a challenge. Behavioral ecotoxicology provides an approach that clearly links disturbances at the biochemical level (e .g., altered neurotransmitters and thyroid hormones) to effects at the population level. These effects may be direct, such as impairment of the search for a sexual partner, care of juveniles, and avoidance of predators or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(62 citation statements)
references
References 107 publications
0
59
1
2
Order By: Relevance
“…Links between behavioural impairment and neurotoxicity revealed by AChE inhibition are well documented for aquatic biota (Amiard-Triquet 2009). In contrast, inhibition of AChE activity was not related to burrowing activity in the present study.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Links between behavioural impairment and neurotoxicity revealed by AChE inhibition are well documented for aquatic biota (Amiard-Triquet 2009). In contrast, inhibition of AChE activity was not related to burrowing activity in the present study.…”
Section: Discussioncontrasting
confidence: 51%
“…Therefore it is important to study the link between the responses of biomarkers at the sub-organismal and supraorganismal levels (Forbes et al 2006). Studies of biomarkers related to energy metabolism, growth or reproduction (De Coen & Janssen 2003, Durou et al 2007b as well as behavioural disturbances (Dell'Omo 2002, Amiard-Triquet 2009) appear particularly promising. Behavioural biomarkers are sensitive tools that help us to assess the impact of contaminants at concentrations far below lethal levels.…”
mentioning
confidence: 99%
“…Different approaches have been proposed to link the responses observed at lower levels of biological organization to the effects at higher levels. Behaviour, an organismlevel response, seems to provide the most promising results (Amiard-Triquet 2009;Dell'Omo 2002 and recently revised by Hellou 2011). In fact, behavioural responses are closely related to physiological and biochemical modifications and have clear connections with population effects via alterations of reproductive success and survival (Amiard-Triquet 2009;Hellou 2011;Wallace and Estephan 2004).…”
Section: Introductionmentioning
confidence: 98%
“…They impact on survival [1] and affect crucial behaviors such as the ability to effectively forage for food, avoid predation, find suitable habitat, compete for resources, and tolerate a number of biotic and abiotic interactions within the surrounding environment [2]. Contaminantinduced behavioral changes can be linked to biochemical and physiological effects at the organism level, which can have flow-on effects at the population level [3]. Therefore, significant changes to crucial behavioral traits of an organism (e.g., foraging behavior, social interaction, and locomotion) may pose a threat to the survival of a population [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral traits can be exploited as toxicity test endpoints and, in some cases, have been demonstrated to be sensitive to contaminant exposure [6,7]. Consequently, behavioral endpoints are increasingly being considered to have high ecological relevance as contaminantinduced changes to an organism's behavior offer insight into potentially major environmental impacts [3]. Previous studies have reported contaminant-induced changes to a number of key behaviors, including predator-prey relationships [8], swimming and mobility [5], and contaminant avoidance [7,9].…”
Section: Introductionmentioning
confidence: 99%